The Effects of Organizational Design on Hospital Nurse Burnout and Performance - Friska Sipayung; Liasta Ginting; Magdalena L. L. Sibarani (Nusantara Science and Technology Proceedings, 2020)
Every company needs an understanding of organizational design to achieve a sustainable competitive advantage. Thus, researching organizational architecture, burnout, and efficiency is important to increase organizational performance, design organizational structures, and maintain a low level of burnout. The findings indicated that respondents had a mostly favorable opinion of organizational architecture, while nurses registered low levels of burnout and high levels of efficiency social assistance questionnaire. and a documentation analysis was used to gather evidence. Study of paths using the Partial Least Squares algorithm The smart PLS method was used to analyze the data in this thesis. (PLS). The findings indicated that respondents had a mostly favorable opinion of organizational architecture, while nurses registered low levels of burnout and high levels of efficiency. In this analysis, the organizational architecture of health care organizations is mechanistic. This is described as a high level of formalization and centralization, and a lack of planning or work experience, among other characteristics. The results showed that organizational design affected burnout. Organizational design affects performance. Organizational design and burnout affect performance.